Dawr al-Muʼassasāt al-ʻĀmmah wa-al-Khāṣṣah fī Tamwīl Ṭibāʻat wa-Nashr al-Turāth: al-Ḥālah al-ʻUmānīyah Namūdhajan - Yūsuf, Muḥammad Maḥmūd ʻAbd Allāh (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
The researcher surveys the various mechanisms for funding the printing of books and manuscripts of the civilizational heritage. The first chapter presents basic definitions, setting out the older and more recent literature on the concept of civilizational heritage and its kinds, the concept of printing and publishing and their kinds, the concept of the public and private institutions connected with printing the civilizational heritage, and the concept of funding the printing of heritage books and manuscripts. The second chapter treats the different kinds of funding for printing and publishing heritage books and manuscripts, and the study proceeds to apply this framework to the Omani case, examining how public bodies and private institutions in Oman have financed the production of heritage works and what this reveals about the sustainability of such publishing.
MHF-PRINT2018-010
Keywords: Heritage publishing; Funding mechanisms; Public institutions; Private sector; Oman; Cultural policy